“Vivenciando etapas do método científico por meio do ensino da botânica em ciências naturais, construção possível em uma escola municipal de Cuiabá MT” - Duarte, Leodenil Alves (2015)
This study aimed to analyze the autonomous performance and participation of the students in a class of 7th grade elementary school in a municipal school of Cuiabá-MT into their construction of scientific knowledge and their interaction with the methodologies applied to teaching of Botany in Natural Sciences, proposing a way for a elaboration of a significant lesson, using a pedagogical teaching tool. The two suggested techniques: decal and leaf epidermal print, both seen into the microscope, indicates a stronger educational tool for teaching botany in elementary school, because it can help to recognize the flora biodiversity of a specific place or region, characterized as a valuable strategy in botany concepts, besides plant manipulations and their structures, engaging and exciting the learning and building the students to the scientific method. The educational product called "world of leaves" brought objectives, the contents, the materials and the structure of the class divided into 5 steps, ranging from botanical collection to the experimentation. As methodological strategy it was possible to work plant morphology and anatomy. Other contents that are inherent to those techniques used are ecology and plant physiology and cytology. This product can be performed in the laboratory or in another area of the school ambience, becoming a dynamic and surprising alternative that provides greater interaction between students and teachers, arousing interest to the relation of biological diversity, experienced day by day, along with the scientific knowledge.